The evolution of the story of Prophet Yusuf (PBUH) in Malay literature and the influence of Arabic literature - Din, Rosma; Yaacob, Adli (IJSSHR, 2024)
This study deals with the evolution of the story of Prophet Yusuf (PBUH) in traditional and modern Malay literature. The story of Prophet Yusuf (PBUH) has been narrated among the stories of prophets in many manuscripts and books of history and Qur’anic exegesis, and his name has also been mentioned in poetry. Moreover, there are academic studies to highlight his holy personality, his beauty, his patience in dealing with all the trials he went through at different stages of his life, and his success in resolving the economic crisis when Allah gave him the authority.